The Effect of Participatory Budgeting on Managerial Performance with Moderating Variables - Saripudin, Saripudin; Siswantoro, Dodik (Universitas Pendidikan Indonesia, 2020)
The research explains both the direct and indirect effects of participatory budgeting on managerial performance by examining organizational culture (people oriented versus job oriented), organizational commitment and perception of innovation that serves as the moderating variables. The research samples are selected by using the purposive sampling method, with the respondents being the public executives at Kantor Pelayanan Perbendaharaan Negara (KPPN). Data for the study was collected from 68 KPPN. The contingency variables were tested either by using the component-based or variance-based structural equation modeling (known as Partial Least Square). The results of the research were consistent with proxy research, which showed that participatory budgeting had a significant influence on managerial performance. Meanwhile, organizational culture (people oriented versus job oriented), organizational commitment, and perception of innovation do not have a significant influence on the relationship between participatory budgeting and managerial performance.Â